Knowledge, Access and Practice: Understanding the Affordable Care Act from the Voices of Somali Immigrant Women in the United States (Glocalism: Journal of Culture, Politics and Innovation, 2018)
Previous literature acknowledges a lack of insurance as a deterrent in seeking healthcare, thus impacting the overall health status of Somali immigrant women (Francis, Griffith, and Leser 2014). This paper builds on the previous literature and addresses the following:a) understand the link between the social determinants of health framework and the Affordable Care Act; b) explore Somali women’s attitudes about the feasibility of access and knowledge of the Affordable Care Act, specifically the Medicaid expansion and health insurance marketplace; c) address Somali women’s encounters with doctors and practitioners post-enactment of the Affordable Care Act. Using interview data from twenty Somali women, common themes elicited were the following: miscommunication among Somali immigrant women and their healthcare providers, feelings of social anxiety and other mental health issues, as well as poor patient and doctor relationships. The project is a community-engaged research study that collects data on individuals’ knowledge with the Affordable Care Act by working with members of several Somali led organizations to identify additional key issues within the community. Furthermore, this project challenges the complexity of adapting and integrating into an unfamiliar culture due to language barriers and approach to medical practices, i.e. views about medical practices may be due to cultural values and beliefs about health. In conclusion, this paper provides demographic data about the impact of health disparities on Somali refugees and immigrants by including how they view access to healthcare, identify barriers to information and care provided by health practitioners, and examine their needs in terms of preventive care.
Keywords: women’s health; immigration; Affordable Care Act; social determinants of health; culture